PEMANFAATAN LIMBAH BATU KAPUR BUKIT SEKAPUK GRESIK SEBAGAI FILLER CAMPURAN AC-BC - Mufidah Rahmawati; Nurani Hartatik; Aditya Rizkiardi; Yudi D. Prasetyo (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
One of the factors that cause easily damaged and potholed road conditions is commonly known as Over Dimension and Over Load (ODOL), and is also one of the causes of the decline in road condition or quality. With the availability of many limestones in Indonesia, it encourages researchers to conduct research on limestone as a filler in the AC-BC mixture using the Marshall test method. The purpose of utilizing limestone filler is how to overcome the limitations of construction materials. Testing Analysis of limestone filler filters obtained a value of 84.06%. Specific gravity testing obtained a value of 2.611. Judging from the flow value at asphalt content of 4.5%, 5.1%, 5.6%, 6.1%, and 6.6% with values of 3.80 mm, 3.97 mm, 3.60 mm, 4.03 mm, and 4.07 mm. Judging from the stability value at asphalt content of 4.5%, 5.1%, 5.6%, 6.1%, and 6.6% with values of 968.6 kg, 1144.6 kg, 1010.9 kg, 1027.6 kg and 991.2 kg. The results showed that the use of Gresik limestone as a substitute for filler in the AC-BC mixture met the specifications that had been set so that it could be used as an alternative filler substitute for highway pavement materials